2020
DOI: 10.1016/j.ijpx.2020.100054
|View full text |Cite
|
Sign up to set email alerts
|

A potent novel vaccine adjuvant based on straight polyacrylate

Abstract: A structure-activity study was conducted to identify the structural characteristics underlying the adjuvant activity of straight ( i.e. non-crosslinked) polyacrylate polymers (PAAs) in order to select a new PAA adjuvant candidate for future clinical development. The study revealed that the adjuvant effect of PAA was mainly influenced by polymer size (Mw) and dose. Maximal effects were obtained with large PAAs above 350 kDa and doses above 100 μg in mice. Small PAAs below 10 kDa had virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…38 Regarding the mechanism of action, our previous studies using SPA09 with the CMV-gB antigen suggested that SPA09 could exert adjuvant activity without apparent interaction with the vaccine antigen. 8 This feature remains to be assessed for the Pre-F-NP and other antigens. Indeed, the polyelectrolyte adjuvants are generally described as dual-functionality adjuvants integrating immunostimulatory and delivery modalities, the latter depending strongly on the ability of the antigen to interact with the adjuvant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Regarding the mechanism of action, our previous studies using SPA09 with the CMV-gB antigen suggested that SPA09 could exert adjuvant activity without apparent interaction with the vaccine antigen. 8 This feature remains to be assessed for the Pre-F-NP and other antigens. Indeed, the polyelectrolyte adjuvants are generally described as dual-functionality adjuvants integrating immunostimulatory and delivery modalities, the latter depending strongly on the ability of the antigen to interact with the adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] We recently introduced a novel adjuvant, termed SPA09, based on high molecular weight linear polyacrylate readily available and easy to formulate with vaccine antigens. 8 In previous studies in mice, SPA09 was found to work as a strong T H 1-type adjuvant when tested with various types of antigens including the recombinant glycoprotein CMV-gB and a Staphylococcus aureus polysaccharide conjugate (patent WO2017218819A1). It was found to be more potent than MF59 (squalene oil-in-water emulsion -Novartis) when tested with CMV-gB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…or intraperitoneally (i.p. ), with 2 μg of gB-CMV [SANOFI Pasteur, prepared as described in ( 34 )], adjuvanted with cationic liposomal formulations (SANOFI Pasteur) including 100 μg 1,2-dioleoyl- sn -glycero-3-ethylphosphocholine (chloride salt) (DOEPC; Avanti Polar Lipids, Alabaster, AL, USA) without (SPA06) or with (SPA10) 17.5 μg 3M-052, in a final volume of 50 μl. These doses were each experimentally defined as optimal in preliminary dose optimization studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the glycoprotein B (gB) of cytomegalovirus ( 34 ) as a model antigen to investigate the mechanisms by which a DOEPC-based cationic liposome formulation including the 3M-052 TLR 7/8 agonist (hereafter named SPA10) exerts its adjuvanticity in comparison to the plain DOEPC-based cationic liposome formulation (hereafter named SPA06), used as control. We show that strong and sustained germinal center (GC) B cell and T follicular helper (T FH ) cell responses are induced by SPA10, associated with a prolonged recruitment/homing of highly activated antigen-loaded monocytes and monocyte-derived dendritic cells (Mo-DCs) toward the injection site and draining lymph nodes (dLNs), and that SPA10-mediated B cell adjuvanticity is type I interferon-independent but NF-κB-dependent.…”
Section: Introductionmentioning
confidence: 99%